Field observations and remote assessment identify climate change, recreation, invasive species, and livestock as top threats to critically imperiled rare plants in Nevada - McClinton, Jamey D.; Kulpa, Sarah M.; Grames, Eliza M.; Leger, Elizabeth A. (Frontiers in Conservation Science, 2022)
Introduction Rare plant species comprise >36.5% of the world’s flora and disproportionately support ecosystem function and resilience. However, rare species also lead global plant extinctions, and unique ecological characteristics can make them vulnerable to anthropogenic pressure. Despite their vulnerability, many rare plants receive less monitoring than is needed to inform conservation efforts due to limited capacity for field surveys. Methods We used field observations and geospatial data to summarize how 128 imperiled, rare vascular plant species in Nevada are affected by various threats. We assessed correlations between threats predicted by geospatial data and threats observed on the ground and asked how historic and current threats compare. Results The most commonly observed threats were from recreation, invasive and non-native/alien species, and livestock farming and ranching. Threat prevalence varied by elevation (e.g., a greater variety of threats at lower elevations, greater threat from climate change observed at higher elevations) and land management. There was a 28.1% overall correlation between predicted and observed threats, which was stronger for some threats (e.g., development of housing and urban areas, livestock farming and ranching) than others. All species experienced extreme climatic differences during 1990-2020 compared to baseline conditions, with the most extreme change in southern Nevada. The average number of threats observed per occurrence increased by 0.024 each decade. Discussion While geospatial data did not perfectly predict observed threats, many of these occurrences have not been visited in over 30 years, and correlations may be stronger than we were able to detect here. Our approach can be used to help guide proactive monitoring, conservation, and research efforts for vulnerable species.